DIGITIZATION OF INDUSTRY: FACTORS, TRENDS, PROSPECTS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
The article defines the main directions of digitization of industry as a factor for the sustainable development of production. A brief overview of the possibilities and risks of the introduction of digital technologies in production, advantages and disadvantages, the origin of digitization and the prospects for its development is given. Because of the study, the main factors of the digital transition of production of the enterprise were identified.